Deconstruction of the Objectification of Female Characters in the Picture Book of Putri Mandalika - Putri Maharani, Faiza; Noviana, Eka (Journal of Arts Education and Design, 2025)
Viewing women as targets of objectification is still tightly grasped by Indonesian culture which is sometimes conveyed through folklore. This research aims to examine one of the folklores of Putri Mandalika as a representation of the deconstruction of women's objectification through picture books. The research was carried out by examining visual elements using the theory of Visual Semiotics which includes Signs, Objects, and Interpretants. The elements other than visuals are in the form of verbal writing. The method used is qualitative descriptive to interpret, analyze, and explain a situation. The results of this study inform that in the picture story book Folklore of Princess Mandalika: A Legend from the Land of Bumi Gora from sasak tribe there are elements of objectification of women where Princess Mandalika is considered an object that can be owned, exchanged, and silenced, but Princess Mandalika succeeded in opposing this and sacrificed for the peace of her people. With more introduction of folktales that resist or without objectification of women, it is possible that Indonesian cultural habits that position women as objects will fade away.